The impact of an electronic educational design using the Ruffini model, accompanied by various educational methods, in learning some basic tennis skills for female students. (Journal of the College of Basic Education, 2023)
Summary of the research:The study aimed to prepare an e-learning design that accompanies various educational methods in learning some basic tennis skills. To identify the effect of using the electronic educational design associated with various educational methods in learning some basic skills in tennis. The researcher used the experimental approach with the design of (two equal groups with a pre and post test) due to its suitability to the nature of the problem and achieving the goal of the research. The research community was identified with female students of the second stage in the College of Basic Education, Department of Physical Education and Sports Sciences - Al-Mustansiriya University for the academic year (2020-2021), and their number is (40) students distributed in three classrooms, and they are integrated into practical lessons in each of the three halls. Either the research sample has It was selected randomly (lottery method), as the research sample amounted to (40) students, with a rate of (20) in the two control groups that use the traditional approach, and the experimental group (20) students that use the designed educational design. The exercises for learning the specific skill were applied and implemented using the method of learning together (cooperative learning) as it is one of the appropriate and suitable methods used in educational designs in general and physical education in particular, by dividing the students into collaborative groups that are heterogeneous in skill performance, as the characteristics of the learners are different as mentioned previously. It is one of the basics of instructional designs. Among the most important conclusions: -1. The instructional design using the Ruffini model contributed to learning some basic tennis skills for the second-stage female students in the experimental group.3. The students of the experimental group excelled in learning some basic tennis skills over the students of the control group.The researcher recommends:1. Work on organizing the content of the study material and designing the classroom environment according to the educational designs using the electronic Ruffini model, in a way that is compatible with achieving the set educational goals.2. Paying attention to providing and supporting e-learning and providing computers in the faculties of physical education and sports sciences in a manner commensurate with the number of learners to ensure the application of modern teaching methods and methods.Tennis for girls.